2012
DOI: 10.1590/s1678-77572012000200022
|View full text |Cite
|
Sign up to set email alerts
|

Influence of combined oral contraceptives on the periodontal condition

Abstract: Most studies investigating the impact of oral contraceptives have been performed some years ago, when the level of sexual hormones was greater than the actual formulations.Objective The aim of this study was to evaluate the effects of current combined oral contraceptives (COC) on periodontal tissues, correlating the clinical parameters examined with the total duration of continuous oral contraceptive intake. Material and methods Twenty-five women (19-35 years old) taking combined oral contraceptives for at lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 26 publications
2
24
0
3
Order By: Relevance
“…The loose connective tissue papillae are running to a long distance in the gingival epithelium near to the keratinous surface with increase in vascularity. These observations could be in accordance with the results of Domingues et al [28] who found that the sulcular bleeding index was significantly higher in the test group of women taking oral contraceptives compared to the control group.…”
Section: Discussionsupporting
confidence: 93%
“…The loose connective tissue papillae are running to a long distance in the gingival epithelium near to the keratinous surface with increase in vascularity. These observations could be in accordance with the results of Domingues et al [28] who found that the sulcular bleeding index was significantly higher in the test group of women taking oral contraceptives compared to the control group.…”
Section: Discussionsupporting
confidence: 93%
“…The main factor that conditions gingival inflammation seems to be the concentration of steroid sex hormones, independently of the amount of dental plaque. [32] The current OCs have a very low concentration of these hormones with probably little influence on gingival inflammation. [2] In this meta-analysis, women who took OCs had BOP significantly higher than that presented by women without OC intake, with a statistically significant association (P < 0.01).…”
Section: Discussionmentioning
confidence: 94%
“…Figure 5a], the five studies [28,29,[31][32][33] that reviewed this parameter showed that OC intake did not affect PD, without a statistically significant relationship (MD = 0.19; 95%: −0.03-0.40, P = 0.08). Six studies [28][29][30][31][32][33] compared the loss of CAL in women who take OCs and those who do not take them [ Figure 5b]. The loss of CAL was greater in women taking OCs, with statistically significant differences (MD = 0.16, 95% CI: 0.01-0.30, P = 0.03).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in periodontal conditions are associated with variations in the levels of these substances 1 . In this respect, the use of oral contraceptives plays an important role 2 , as these drugs modify the estrous cycle to prevent pregnancy. Nevertheless, it seems that estrogen and progesterone receptors located in the gingival tissue allow a greater accumulation of immunoinflammatory products, altering defense responses to microbial biofilm challenges 3 .…”
Section: Introductionmentioning
confidence: 99%